Measuring Information Security Awareness at Muhammadiyah University of Palembang Using HAIS-Q - M. Rizky Mahendra; Catur Eri Gunawan; Freddy Kurnia Wijaya (Universitas Mohammad Husni Thamrin, 2026)
The rapid development of information technology has transformed various aspects of human life, including the way people work, interact, and learn. This progress has driven increased efficiency in daily activities, especially in higher education. The increasing dependence of the academic community on digital systems in academic and administrative activities has also increased information security risks in higher education. Muhammadiyah University of Palembang, which is undergoing a digital transformation, faces challenges in building information security awareness among its users. This study aims to measure the level of information security awareness of the academic community using quantitative methods through the Human Aspects of Information Security Questionnaire (HAIS-Q), which covers the dimensions of Knowledge, Attitude, and Behavior in 7 focus areas. The measurement stages refer to the Kruger & Kearney model with the determination of the importance weight of each focus area using the Analytic Hierarchy Process (AHP) method. The questionnaire data were analyzed descriptively. The results showed that the level of information security awareness was in the moderate category with a total score of 74.15%. The Knowledge dimension obtained a score of 70.39%, Attitude 75.63%, and Behavior 75.82%. The lowest scores were found in the sub-focus area of ​​internet and social media usage behavior. This finding underscores the need for strategic interventions in the form of ongoing training, outreach, and technical policy development to strengthen information security awareness within universities, particularly in areas with low levels of awareness.